Hard X‐ray polarizer to enable simultaneous three‐dimensional nanoscale imaging of magnetic structure and lattice strain. (9th August 2016) - Logan, Jonathan; Harder, Ross; Li, Luxi; Haskel, Daniel; Chen, Pice; Winarski, Robert; Fuesz, Peter; Schlagel, Deborah; Vine, David; Benson, Christa; McNulty, Ian
Abstract : The performance of a diamond X‐ray phase retarder to enable the production of circularly polarized X‐rays has been quantitatively measured and magnetic dichroism contrast in transmission and diffraction geometries has been demonstrated. Feasibility tests for dichroic Bragg coherent diffractive imaging experiments were performed and showed that the diamond X‐ray phase retarder does not produce significant distortions to the X‐ray wavefront and that Bragg coherent diffractive imaging reconstructions are achievable. Abstract : Recent progress in the development of dichroic Bragg coherent diffractive imaging, a new technique for simultaneous three‐dimensional imaging of strain and magnetization at the nanoscale, is reported. This progress includes the installation of a diamond X‐ray phase retarder at beamline 34‐ID‐C of the Advanced Photon Source. The performance of the phase retarder for tuning X‐ray polarization is demonstrated with temperature‐dependent X‐ray magnetic circular dichroism measurements on a gadolinium foil in transmission and on a Gd5 Si2 Ge2 crystal in diffraction geometry with a partially coherent, focused X‐ray beam. Feasibility tests for dichroic Bragg coherent diffractive imaging are presented. These tests include (1) using conventional Bragg coherent diffractive imaging to determine whether the phase retarder introduces aberrations using a nonmagnetic gold nanocrystal as a control sample, and (2) collecting coherent diffraction patterns of a magnetic Gd5 Si2 Ge2 nanocrystal with left‐ and right‐circularly polarized X‐rays. Future applications of dichroic Bragg coherent diffractive imaging for the correlation of strain and lattice defects with magnetic ordering and inhomogeneities are considered.